Acts of Communion: Encountering taste in Reckless Sleepers' The Last Supper. (3rd October 2017) - Pinchbeck, Michael; Westerside, Andrew
Abstract : An article about the aesthetics, politics and dramaturgy of taste implicit in Reckless Sleepers'The Last Supper (2003). The authors explore notions of gustatory taste and the multi-sensory potential of serving food in performance and the ethics of (mis)representation of real life events; the assassination of the Romanovs and Che Guavara proving to be the most unreliable narratives. The piece sits between fact and fiction, the found and the fabricated, and is punctuated with the arrival of the real last suppers of convicted felons. The work speaks from a primarily western religious perspective, inspired by Da Vinci'sLast Supper (1498) and the act of communion that takes place in church services. In this way, it leans towards an occidental, spiritual notion of taste, where transubstantiation allows the rice paper script to become both the body of Christ and the symbol of his own last supper. Nietzsche's notion of intoxication comes into play as performers and audience share wine, or blood, and drink to absent friends. The article proposes that the piece enacts a dramaturgy much like a meal, where conversation ebbs and flows, and a sense of togetherness, or act of communion, is engendered. The authors posit that the tacit contract with the audience is redrawn by food as both an aesthetic and dramaturgical encounter. As such, it becomes an invocation (or intoxication) of taste, mortality and last-ness that continues to resonate thirteen years after its devising. Both Pinchbeck and Westerside wrote about this performance when they first saw it at the same venue in 2006, both conducted interviews with members of the Reckless Sleepers, Mole Wetherell and Tim Ingram, for their ongoing research into dramaturgy, aesthetics and taste in contemporary performance. Now this research is woven together into a tapestry of reflections on the piece, a pentimento of memories.